Combining Scenario Workshops and Participatory System Dynamics Modelling to Study Food Security. A case study with farmers in Zambia - Ferreira, Maria Eduarda Bruel de Salles (2017)
Food security, which affects mainly developing countries, is a worldwide problem that has called the attention of the economic, political and scientific community. Achieving food security is a very complex process that involves not only the ability of farming but also a constant adaptation to natural phenomena, as for example, rainfall patterns. Limited knowledge and access to information and technologies, restrict the capacity of local farming communities to achieve food security. Furthermore, there is a lack of suitable methods and tools for involving stakeholders, such as farmers, in the development and assessment of food policies and their long-term system-wide effects. The main goal of this research is to investigate how the use of mixed-methods – scenarios and participatory System Dynamics (SD) modelling – are capable of improving understanding and an integrative view of food systems, serving as a lever for supporting food security decision-making processes. Additionally, this research aims to answer the following two questions: i) How can scenarios and participatory SD be used together to study plausible futures of food security involving smallholder farmers in developing countries?; ii) What are the possible policy pathways to avoid undesirable situations and to stimulate desirable ones, in a context of subsidence farming in Sub-Saharan African countries?. For this specific purpose, a group of smallholder farmers in Zambia was analyzed as a case study. First, a workshop was implemented in which a scenario of poor rainfall and no government help was developed. In order to achieve food security, participants had to find policy proposals and pathways to avoid or to overcome this undesired scenario. Subsequently, from the scenario workshop data, causal loop diagrams (CLD) were built using a systematic coding process. The next steps were to analyse policy proposals through a cross-impact analysis and develop an outline of pathways to study the complementarity and compatibility of such proposals. The 11 policy proposals were Charcoal Business; Livestock Business; Groundnuts Business; Gardening; Loan; Piecework; Land (productive land); Rental Business; Partnership; Legislation for Deforestation/Afforestation; and, Retention Basins/Drilling Boreholes. Finally, it was possible to design an innovative Action Plan that shows the pathways and the pace at which each proposal may achieve food security. It was concluded that scenario workshop and participatory SD may tightly coupled since these methods complement each other, stimulating system thinking and co-creation of knowledge. Scenario workshops are a disruptive and exploratory method, as it allows to elicit creative and plausible images from participants. Participatory SD supports decision-making processes by analysing policy proposals and its pathways, leading to the elaboration of joint action plans. In the Zambian case, from the 11 plausible policy proposals, it was found that Piecework enables a swifter path to achieve food security, while Rental Business would be the slowest. Additionally, it was found that some of the policy proposals could be reinforced if implemented together, while others, such as Charcoal Business and Legislation for Deforestation/Afforestation, did not show such potential. A follow-up survey with workshop participants showed that they were following the Action Plan, confirming the preference for the short-term policy proposal pathways.